Sustainable Branding Strategy: How Green Image and Trust Influence Purchase Intention in The Bottled Water Industry - Giat Mahathir Jasman; Fakhri, Erie Awalil (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
The increasing consumption of bottled water has raised environmental concerns, especially regarding plastic waste generation, which demands companies to implement sustainable business strategies. This study aims to examine the influence of green brand image and green brand trust on purchase intention in the context of Le Minerale, a leading bottled water brand in Indonesia. This research used a quantitative explanatory approach with a probability sampling technique through simple random sampling. Data were collected through a questionnaire distributed to 170 respondents from Generation Z in Malang City. The data were analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM). The results indicate that green brand image has a positive and significant effect on purchase intention, meaning that a strong environmentally friendly brand image increases consumer interest in purchasing the product. Furthermore, green brand trust also has a positive and significant effect on purchase intention, indicating that consumer trust in the brand's environmental commitment enhances purchase intention. This study implies that companies need to strengthen sustainable branding strategies to foster consumer trust and environmentally friendly brand perception.